Pengaruh Laju Alir Biogas dan Ukuran Partikel Pembentuk Pelet terhadap Penyisihan Karbon Dioksida (CO2) dalam Biogas dengan Proses Adsorpsi - Desorpsi Menggunakan Adsorben Berbasis Zeolit Alam untuk Peningkatan Kualitas Biogas - Sidabutar, Rivaldi; Trisakti, Bambang; Irvan (Talenta Publisher (Universitas Sumatera Utara), 2023)
Adsorption is the process of fluid molecules contacting the surface of a solid material. This study aims to remove carbon dioxide (CO2) gas in biogas using natural zeolite-based adsorbent pellets by adsorption and desorption of CO2 from the adsorbent using air. CO2 removal was carried out to determine the percentage of CO2 removal efficiency with variations in biogas flow rates (100 mL/minute, 300 mL/minute, and 500 mL/minute) and variations in the type of adsorbent pellets (particle size, activation time, calcination time, and dealumination activation treatment). Determination of the percentage of CO2 removal is carried out by flowing the biogas into the column and contacting it with the adsorbent continuously for 30 minutes and the output gas is collected in a gas collector to analyze the remaining CO2 content. The results showed that the best CO2 removal was 97.7% using an adsorbent with a particle size of 140 mesh, 4 hours of calcination, 90 minutes of activation time, and dealumination activation at a flow rate of 100 mL/minute. The breakthrough characteristic curve presents the characteristic â€œSâ€ profile at constant flow rate (100 mL/minute).